The enduring library - Gorman, Michael (American Library Association, 2003)
The way we live now : libraries today – Communication technology, 1875 to now – Communication technology and libraries today – Reading in a digital world – The nature of the web – Reference work in technologically advanced libraries – Cataloguing in the 21st century – Challenges of the future – The future of libraries : a research agenda – Information overload and stress – Seeking harmony and balance.
The way we live now : libraries todayCommunications technology, 1875 to now – Communications technology and libraries today – Reading in a digital world – The nature of the web – Reference work in technologically advanced libraries – Cataloguing in the twenty-first century – Challenges of the future – The future of libraries : a research agenda – Information overload and stress : the ailments of modern living – Seeking harmony and balance.
Keywords: Libraries and society; Libraries; Library science; Librarians